2008
DOI: 10.1186/cc7017
|View full text |Cite
|
Sign up to set email alerts
|

Strict glycaemic control in patients hospitalised in a mixed medical and surgical intensive care unit: a randomised clinical trial

Abstract: IntroductionCritically ill patients can develop hyperglycaemia even if they do not have diabetes. Intensive insulin therapy decreases morbidity and mortality rates in patients in a surgical intensive care unit (ICU) and decreases morbidity in patients in a medical ICU. The effect of this therapy on patients in a mixed medical/surgical ICU is unknown. Our goal was to assess whether the effect of intensive insulin therapy, compared with standard therapy, decreases morbidity and mortality in patients hospitalised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
157
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(168 citation statements)
references
References 19 publications
1
157
0
10
Order By: Relevance
“…Our analysis included 14,495 patients from 27 studies 128, 330, 331, 332, 337, 338, 339, 340, 341, 342, 343, 344, 345, 346, 347, 348, 349, 350, 351, 352, 353, 354, 355, 356, 357, 358, 359. None of the studies were especially prone to bias.…”
Section: Cq14: Blood Glucose Managementmentioning
confidence: 99%
“…Our analysis included 14,495 patients from 27 studies 128, 330, 331, 332, 337, 338, 339, 340, 341, 342, 343, 344, 345, 346, 347, 348, 349, 350, 351, 352, 353, 354, 355, 356, 357, 358, 359. None of the studies were especially prone to bias.…”
Section: Cq14: Blood Glucose Managementmentioning
confidence: 99%
“…However, other studies did not get a similar result [40][41][42][43][44][45][46], with some stopped for safety due to hypoglycemia [44] or unintended protocol violations [46]. The recent NICE-SUGAR study [45] reported an increase in mortality in the TGC arm with a lower glycemic target, but was also subject to criticism of its treatment approach, analysis and randomisation methods [47][48][49][50].…”
Section: Hyperglycemia Hypoglycemia Tgc and Patient Mortality Outcomementioning
confidence: 99%
“…However, repeating these results has been difficult, and thus the role of tight glyceamic control during critical illness and suitable glycaemic ranges have been under scrutiny in recent years [4,5,6,7,8,9,10,11]. However, conclusions are varied with both success [1,12,13,14], failure, [15] and, primarily, no clear outcome [16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%